The Implementation of Restorative Justice In Criminal Proceedings At The Cirebon District Court - Muslikah Muslikah; Alip Rahman (Ann Publisher, 2026)
Background. Certain criminal offenses may be processed using a restorative justice approach. Judges apply guidelines for adjudicating criminal cases based on restorative justice through the restoration of the victim’s losses and/or the restoration of relationships between the defendant, the victim, and the community through their rulings. Methods. The approaches used in this research are the philosophical-juridical and normative-juridical approaches, employing a positivist paradigm—that is, using an objective, data-driven scientific approach to seek accurate truth. The philosophical-juridical approach is a legal research method that examines the enforcement of law from a philosophical perspective, analyzing the interplay between criminal law and restorative mechanisms. Conclusion. The mechanism for the Restorative Justice process during criminal proceedings in court is regulated under Law No. 1 of 2023 in conjunction with Law No. 20 of 2025 and is further regulated in Government Regulation, namely PERMA No. 1 of 2024. Judges adjudicate criminal cases using Restorative Justice in accordance with the principles of restoration of the situation, strengthening of rights, the needs and interests of the victim, the responsibility of the defendant, criminal punishment as a last resort, consensuality, transparency, and accountability. However, the application of the principles of Restorative Justice is not intended to eliminate criminal liability. Implementation. The implementation of Restorative Justice practices in several judgments at the Cirebon District Court is in accordance with PERMA No. 1 of 2024 on Guidelines for Adjudicating Criminal Cases Based on Restorative Justice , in Chapter III: Procedures for Adjudicating Criminal Cases Based on Restorative Justice.